2017
DOI: 10.1093/europace/eux107
|View full text |Cite
|
Sign up to set email alerts
|

Family history of atrial fibrillation as a predictor of atrial substrate and arrhythmia recurrence in patients undergoing atrial fibrillation catheter ablation

Abstract: The presence of a 1st-degree family member with AF does not impact the clinical outcomes of catheter ablation for paroxysmal AF. However, a positive family history is associated with worse arrhythmia free survival in patients with PeAF. This finding is not explained by differences in clinical characteristics, atrial substrate assessed by voltage maps or ablation characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The recent work by Khan et al compiled 134 randomized studies and reported that 4.5% of AF patients had obstructive sleep apnea, 35.8% had coronary artery disease (CAD), 66.4% had diabetes mellitus, 75.4% had hypertension, 12.7% had dyslipidemia, 9.7% had chronic kidney disease (CKD), 44% had heart failure (HF), 45.5% had cerebrovascular accidents, and 9% had the chronic obstructive pulmonary disease (COPD) [ 13 ]. Indeed, multimorbidity is common in patients with AF and both non-cardiac and cardiac comorbidities clusters may be associated with an increased risk of major adverse outcomes of different manners [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent work by Khan et al compiled 134 randomized studies and reported that 4.5% of AF patients had obstructive sleep apnea, 35.8% had coronary artery disease (CAD), 66.4% had diabetes mellitus, 75.4% had hypertension, 12.7% had dyslipidemia, 9.7% had chronic kidney disease (CKD), 44% had heart failure (HF), 45.5% had cerebrovascular accidents, and 9% had the chronic obstructive pulmonary disease (COPD) [ 13 ]. Indeed, multimorbidity is common in patients with AF and both non-cardiac and cardiac comorbidities clusters may be associated with an increased risk of major adverse outcomes of different manners [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…All these data confirm the multi-complexity of the AF population, but our results underline the interest of stratification to optimize the understanding of AF and also to possibly optimize the management, whether pharmacological or non-pharmacological, of AF. Indeed, recent guidelines have recommended a more holistic or integrated approach to AF care, including stroke prevention, patient-centered decisions on rate- or rhythm control, and the optimization of comorbidities [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Adherence to such an approach has been associated with improved clinical outcomes [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zöller et al 20 demonstrated that the risk of recurrent lone AF hospitalization was 23% higher for individuals with affected parents and 30% higher for those with affected siblings in a nationwide family study in Sweden. A single‐centered, small‐sized (with 132 patients with FAF), retrospective study demonstrated that a positive FAF was associated with an increased risk of arrhythmia recurrence in patients with persistent AF, but not in paroxysmal AF patients after a single catheter ablation 13 . In the contrary, Shoemaker et al 21 used genetic susceptibility for AF as a surrogate of FAF, and found no association between high AF genetic susceptibility and recurrence after de novo AF ablation.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether FAF has any impact on the risk of AT recurrence after AF ablation. One study has ever reported higher risk of AT recurrence in patients with FAF after initial catheter ablation, but the study was limited by small sample size 13 . In this study, we used data from a large Chinese AF cohort (China‐AF study) to determine whether FAF is a risk factor of AT recurrence after AF ablation.…”
Section: Introductionmentioning
confidence: 99%
“…2 The heterogeneous nature of AF requires that physicians treat each patient according to their own risk profile. [31][32][33] However, patients may also present without clinical risk factors, and still develop AF. Prior studies show that a lower clinical risk profile is associated with higher AF genetic susceptibility.…”
Section: The Fifth Paradigm-using Atrial Fibrillation Genetics To Develop New Therapeuticsmentioning
confidence: 99%